Cardiolipotoxicity, Inflammation, and Arrhythmias: Role for Interleukin-6 Molecular Mechanisms - Alí, Alessandra; Boutjdir, Mohamed; Aromolaran, Ademuyiwa S. (Frontiers in Physiology, 2019)
Fatty acid infiltration of the myocardium, acquired in metabolic disorders (obesity, type-2 diabetes, insulin resistance, and hyperglycemia) is critically associated with the development of lipotoxic cardiomyopathy. According to a recent Presidential Advisory from the American Heart Association published in 2017, the current average dietary intake of saturated free-fatty acid (SFFA) in the US is 11-12%, which is significantly above the recommended <10%. Increased levels of circulating SFFAs (or lipotoxicity) may represent an unappreciated link that underlies increased vulnerability to cardiac dysfunction. Thus, an important objective is to identify novel targets that will inform pharmacological and genetic interventions for cardiomyopathies acquired through excessive consumption of diets rich in SFFAs. However, the molecular mechanisms involved are poorly understood. The increasing epidemic of metabolic disorders strongly implies an undeniable and critical need to further investigate SFFA mechanisms. A rapidly emerging and promising target for modulation by lipotoxicity is cytokine secretion and activation of pro-inflammatory signaling pathways. This objective can be advanced through fundamental mechanisms of cardiac electrical remodeling. In this review, we discuss cardiac ion channel modulation by SFFAs. We further highlight the contribution of downstream signaling pathways involving toll-like receptors and pathological increases in pro-inflammatory cytokines. Our expectation is that if we understand pathological remodeling of major cardiac ion channels from a perspective of lipotoxicity and inflammation, we may be able to develop safer and more effective therapies that will be beneficial to patients.